Transparency of Village Fund Management - Herman H; Ilham Ilham (Universitas Negeri Makassar, 2021)
Transparency of Village Fund Management in Sunggumanai Village, Gowa Regency. Thesis. Public Administration Study Program. Postgraduate Program. Makassar State University. This study aims to find out and describe the Transparency of Village Fund Management in Sunggumanai Village, Gowa Regency. This research method uses a Qualitative approach with data collection techniques using interactive models, namely data collection, data condensation, data presentation, and conclusion verification. The results showed that 1). The availability of adequate information about village funds is considered effective. 2). The knowledge and insights of the community about village funds are considered to have been carried out effectively. 3). Increasing public trust in the management of village funds is considered to have been running effectively. 4). Increasing community participation in village fund activities is considered effective. Overall, it can be understood that the Transparency of Village Fund Management in Sunggumanai Village, Gowa Regency, has been effectively achieved by openness in the preparation of village fund programs, availability of information access through village forums, billboards, and the inscription making of every completed project development. So that the response of Sunggumanai villagers to the implementation of village government is going well, allocating in the performance of village funding programs has increased public confidence in the village government, the result of village development is increasingly advanced. Creating a good relationship between the community and the government through community empowerment with a labor-intensive model of the local village community is allowed to implement village funding programs both in physical and non-physical development.